Kesenjangan Komunikasi Pemasaran Desa Wisata Berbasis Kearifan Lokal: Analisis Komparatif Multikasus di Sumatera Barat - Gilang Surendra; Tia Kharina Elvonny; Dion Eriend (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
West Sumatra hosts 456 tourism villages rich in Minangkabau local wisdom, yet tourist visits remain highly concentrated in urban centers while most rural villages face significant marketing communication gaps. This study aims to critically and comparatively analyze the marketing communication gaps of local wisdom-based tourism villages in West Sumatra, positioning Desa Wisata Kubu Gadang as the success benchmark. Methodologically a qualitative comparative literature (documentary) study with an analytical-comparative multi-case design, this research examines six tourism villages (Kubu Gadang, Guranjhil, Nagari Sumpu, Marapalam, Apar, and Sarugo) through literature review of academic publications and public documents, analyzed using qualitative content analysis with cross-case synthesis. The findings identify six determinant factors for successful marketing communication: (1) the presence of change agents bridging tradition and innovation; (2) the ability to create viral content from local wisdom; (3) integration of tourism packages within coherent marketing narratives; (4) institutional diversification; (5) academic collaboration; and (6) adequate digital infrastructure. Kubu Gadang's 425% visitor increase and ADWI 2023 Advanced Village status indicate that creative commodification of local wisdom constitutes the most effective marketing communication strategy, with human agency and creative innovation proving more determinative than structural factors alone.